Gestational Weight Gain among women with different pre-pregnancy BMI and its relation with Birth Weight of Neonates (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aim: To find out the relationship between gestational weight gain among women with different  early pregnancy Body Mass Index and birth weight of neonates.Methods: This is an analytical observational hospital based study. Singleton pregnancy within 10 weeks of gestation were included in the study and they were followed at term. First trimester Body Mass Index was calculated and the women were divided in to underweight, normal weight, overweight and obese according to World Health Organization classification. Total gestational weight gain was calculated and compared according to the American College of Obstetrics guideline. The birth weight of neonate was recorded soon after the delivery and the relation between gestational weight gain and birth weight of the neonate was studied.Results: Total 228 women were analyzed. Most of the women (69%) had normal Body Mass Index with the mean gestational weight gain of 10.59±4.317 kg and the mean birth weight 3.03±0.487 kg. Underweight and normal weight women had less pregnancy weight gain; overweight women had slightly higher weight gain whereas obese women had weight gain as per the recommendation. The birth weight of neonate was higher in overweight and obese women (p=0.004) but without positive correlation.Conclusions: The gestational weight gain is not related to the birth weight of neonates but related to the early pregnancy BMI.